Emerging Roles of Tripartite Motif-Containing Family Proteins (TRIMs) in Eliminating Misfolded Proteins - Zhang, Litian; Afolabi, Lukman O.; Wan, Xiaochun; Li, Yang; Chen, Liang (Frontiers in Cell and Developmental Biology, 2020)
Protein quality control (PQC) is pivotal for eukaryotic cells to eliminate misfolded proteins and maintain cellular homeostasis. A decreased or increased capacity of PQC is associated with various diseases, e.g. neurodegenerative diseases and cancers. Recently, increasing evidences have suggested that tripartite motif-containing family proteins (TRIMs) are the key players in PQC regulation. Most TRIMs are E3 ubiquitin ligases, such as TRIM11/19/25, which could effectively remove the cellular misfolded proteins or protein aggregates through the ubiquitination modifications UPS pathway. In this review, we summarized the participation of TRIM members in misfolded proteins elimination with distinct pathways, including the ubiquitin-proteasome system (UPS), autophagy system and ER-associated degradation (ERAD).